Metagenomic Next-Generation Sequencing Can Clinch Diagnosis of Non-Tuberculous Mycobacterial Infections: A Case Report - Zhu, He; Zhu, Min; Lei, Jia-Hui; Xiao, Ya-Li; Zhao, Li-Min (Frontiers in Medicine, 2021)
Non-tuberculou Mycobacteria (NTM) is ubiquitous in the environment and is conditional pathogen. Due to NTM and Mycobacterium tuberculosis belong to the genus Mycobacterium, their pathogenic mechanisms and clinical manifestations are similar. Therefore, NTM can cause tuberculosis-like lesions and lead to misdiagnosis. Early diagnosis and treatment greatly improve prognosis. However, traditional pathogenic microorganism detection has limitations, and it is difficult to accurately identify strains in clinical practice. Here, we report a 65-year-old man with NTM who presented with recurrent fever and cough. Computed tomography of the chest revealed a lung infection. The previous improper diagnosis and treatment did not improve his condition. With the aid of metagenomic next-generation sequencing, the pathogen was identified as Mycobacterium avium complex. Subsequently, he received accurate treatment and made significant improvements in clinical and radiology.